A review of the genus Elephantomyia Osten Sacken from China, with descriptions of two new species (Diptera, Limoniidae) - Zhang, Xiao; Li, Yan; Yang, Ding (Zootaxa, 2015)
The genus Elephantomyia from China is reviewed. Two species, E. laohegouensis sp. nov. and E. tianmushana sp. nov., are described as new to science. One species, E. inulta Alexander, 1938, is recorded for China for the first time. Seven known Chinese species/subspecies are redescribed and illustrated. A key to the species of the genus Elephantomyia from China is given.